Ius Constituendum foreign fintech investment (post/after) employment law to accelerate Indonesian economic development - Saparyanto; Imanullah, Moch. Najib (Technium Social Sciences Journal, 2022)
Investment is an activity to utilize funds owned by investing in productive projects/joint ventures, either directly or indirectly, with the hope that apart from obtaining initial capital in the future, f course, the owner of the capital will also benefit from the investment concerned. Financial Technology (FinTech) is an alternative solution to meet the public’s needs for financial services. This study aimed to explore positive laws governing fintech-based foreign investment, in order to develop futuristic and doelmatigheid law. To achieve this goal, normative legal research is carried out, which makes the system of norms and legal rules as the centre of study related to legal events. The data used in the study was secondary data, consisting of primary legal materials containing statutory regulations, and secondary legal materials that were the result of relevant legal research (journals), books, and scientific works on the internet. A literature study was used as a technique in obtaining data, which was then processed by descriptive analysis methods to get conclusions. The results of the study showed that the current fintech regulation in Indonesia is not ideal because there are several legal voids, among which there are no laws and regulations governing business which are the legal protection for the Financial Services Authority (OJK) Regulations and BI Regulations as the implementers. Furthermore, the role of OJK in conducting supervision has not been maximized and there are no firm, clear and comprehensive rules regarding this fintech. Especially about fintech that has foreign capital in it. In addition, the community’s legal culture/culture is not familiar yet with fintech-based foreign investment. For this reason, it is recommended o reconstruct the regulation, it is very necessary to increase the public’s understanding of fintech-based foreign investment.